Host-specific vascular endothelial cell responses to Angiostrongylus vasorum: a comparative in vitro study in red foxes (Vulpes vulpes) and domestic dogs - Eisenhut, Belinda; Wittwer, Aline; Schnyder, Manuela; Oehm, Andreas W. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCanine angiostrongylosis, caused by Angiostrongylus vasorum, affects dogs and red foxes, with dogs developing cardiopulmonary and coagulation disorders, while foxes remain mostly subclinical.MethodsThis study examined aortic endothelial cell responses from both species to A. vasorum adult full somatic antigen extracts, first-stage larval (L1) antigen, and adult excretory-secretory products (ESP). Differential gene expression of interleukins (IL) -6, -10, and -33, intercellular adhesion molecule 1 (ICAM-1), vascular adhesion molecule 1 (VCAM-1), endothelial selectin (E-selectin), platelet selectin (P-selectin), vascular endothelial growth factor (VEGF), and monocyte chemoattractant protein 1 (MCP-1) was assessed via reverse transcription quantitative PCR (RT qPCR) after four and 24 hours of antigen exposure.ResultsFour hours post ESP stimulation, IL-10 increased in dogs (1.8-fold) but decreased in foxes (0.4-fold). IL-33 declined in both, (0.9-fold vs. 0.7-fold, respectively). VCAM-1 was upregulated more in foxes (3.5-fold vs. 1.2 in dogs). Following adult antigen exposure, P-selectin, ICAM-1, and VCAM-1 increased in fox more than in dog cells (1.4, 1.7, and 3.1-fold vs. 0.9, 0.5, and 0.7-fold, respectively). L1 antigen downregulated IL-10 and MCP-1 in dogs (0.7 and 0.8-fold) but upregulated them in foxes (2.1 and 1.1-fold). Twenty-four hours after ESP stimulation, ICAM-1 decreased in dogs (0.8-fold) but increased in foxes (1.4-fold). VCAM-1 was downregulated in dogs (0.6-fold) but upregulated in foxes (12.9-fold). Adult antigen exposure upregulated P-selectin in both species, more in foxes (4.8-fold) than in dogs (1.9-fold). ICAM-1 was downregulated in dogs (0.8-fold) but upregulated 7.5-fold in foxes. L1 antigen stimulation caused the most substantial differences between species: IL-6 was upregulated more in dogs (4.7-fold) than foxes (1.2-fold). E-Selectin was upregulated in dogs (12.8-fold) but downregulated in foxes (0.2-fold). P-selectin increased more in dogs (10.0-fold) than in foxes (1.7-fold). ICAM-1 was downregulated in dogs (0.6-fold) but upregulated in foxes (2.6-fold), as was VCAM-1 (0.7-fold and 3.1-fold). VEGF was upregulated 9.5-fold in dogs after adult antigen exposure, and 7.6-fold after L1 antigen exposure, while it remained rather unchanged in foxes (0.9-fold and 1.0-fold, respectively).DiscussionThese findings corroborate that foxes have developed mechanisms for a regulated immune response following A. vasorum exposure, while dogs exhibit a higher pro-inflammatory reaction, contributing to severe clinical outcomes. Host-parasite co-evolution may explain differences in the pathogenesis and clinical presentation of canid angiostrongylosis.